(untitled) (Journal of Science and Technology, 2016)
The form and orientation of a building can have an effect on energy performance. The difficulty has been to find the most energy efficient form-aspect ratio. In this paper, a volume with differ-ent aspect ratios has been used to investigate the effect on energy performance (cooling load). The volume used is of the same construction and an hourly dynamic simulation programme was used for the analysis. It was evident that the square form was the most energy efficient whiles elongated forms used much energy. However, since spaces could warm up when oriented to-wards the east and west, the authors further recommend a detailed look into the function of spaces in design schemes and the use of simulation for design alternatives.